2021
DOI: 10.3389/fneur.2021.643646
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Emotional Disturbances Due to COVID-19: An Exploratory Study in the Rehabilitation Setting

Abstract: The coronavirus disease 19 (COVID-19) can cause neurological, psychiatric, psychological, and psychosocial impairments. Literature regarding cognitive impact of COVID-19 is still limited. The aim of this study was to evaluate cognitive deficits and emotional distress among COVID-19 and post–COVID-19 patients who required functional rehabilitation. Specifically, this study explored and compared cognitive and psychological status of patients in the subacute phase of the disease (COVID-19 group) and patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 39 publications
2
43
0
13
Order By: Relevance
“…However, the MoCA proved to be slightly more sensitive than the MMSE in detecting sub-clinical cognitive changes, as well as abler than the MMSE in differentiating between diverse levels of cognitive efficiency [ 4 ]. These findings are in line with previous ones on the MoCA—which were also paralleled by neurofunctional evidence [ 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the MoCA proved to be slightly more sensitive than the MMSE in detecting sub-clinical cognitive changes, as well as abler than the MMSE in differentiating between diverse levels of cognitive efficiency [ 4 ]. These findings are in line with previous ones on the MoCA—which were also paralleled by neurofunctional evidence [ 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the MoCA proved to be slightly more sensitive than the MMSE in detecting sub-clinical cognitive changes, as well as abler than the MMSE in differentiating between diverse levels of cognitive efficiency [ 4 ]. These findings are in line with previous ones on the MoCA—which were also paralleled by neurofunctional evidence [ 4 , 9 ]. Such differential performances of the two screeners appear to be also supported by the fact that, when considering different ability levels, their agreement was higher for patients whose putative cognitive impairment could be more easily detected (RCD+).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive decline was not only observed during acute infection, but there are also reports of persistent cognitive impairment after recovering from COVID-19, as MOCA abnormalities were detected in a group of post-COVID-19 patients [ 116 ]. Another study confirmed that cognitive deficits persisted in 70% of COVID-19 patients for at least 1 month after hospital discharge [ 116 , 117 ]. Similarly, 46 of 57 recovering COVID-19 patients (81%) had signs of cognitive impairment [ 13 , 118 ].…”
Section: Chaptermentioning
confidence: 99%
“…( 35 ) The most frequent profile of post–COVID-19 cognitive impairment involves executive function and may be detected from 4 weeks after diagnosis (subacute or convalescent phase) and even after 12 weeks (persistent symptomatology). ( 36 ) Most published studies use cognitive screening tests (eg, the MoCA or Mini–Mental State Examination), administered either in person ( 37. , 38.…”
Section: Profile Of Post–covid-19 Cognitive Impairmentmentioning
confidence: 99%